Translating the text of Quran into Kazakh language and the methods of interpretation - Қыдырбaев, Қ.; Молдaхметов, Р. (Journal of Oriental Studies, 2018)
In this article, first of all the history of the translation of the Qur’an into the Kazakh language is presented. Here you can find out when and by whom the holy book was interpreted into our native language. In this article you can also find an answer to when and how the Soviet Union eradicated some scripts that had been translated into the Kazakh language. Furthermore, in this research other aspects are discussed such as below listed: 1. Types of translation of the Holy Quran; 2. The two main objectives of the Qur’an; 3. The linguistic features of the Arabic language; 4. The approaches to understand and interpret the Quran; 5. The language of the Qur’an is a pinnacle of the classical Arabic language; 6. What is the method of semantics. The above mentioned seven research subjects thoroughly expound the topic of this article. The main purpose of this article is to convey to the readers in a comprehensible way how to translate and interpret the Quran in Kazakh.